Molecular Scale Description of Anion Competition on Amine-Functionalized Surfaces - Rock, William; Oruc, Muhammed E.; Ellis, Ross J.; Uysal, Ahmet (AMER CHEMICAL SOC, 2016)
Many industrial and biological processes involve the competitive adsorption of ions with different valencies and sizes at charged surfaces; heavy and precious metal ions are separated on the basis of their propensity to adsorb onto interfaces, often as anionic ion clusters (e.g., [MClx](n-)). However, very little is known, both theoretically and experimentally, about the competition of factors that drive preferential adsorption, such as charge density or valence, at interfaces in technologically relevant systems. There are even contradictory pictures described by interfacial studies and real life applications, such as chlorometalate extractions, in which charge diffuse chlorometalate ions are extracted efficiently even though charge dense chloride ions present in the background are expected to occupy the interface. We studied the competition between divalent chlorometalate anions (PtCl62- and PdCl42-) and monovalent chloride anions on positively charged aminefunctionalized surfaces using in situ specular X-ray reflectivity. Chloride anions were present in vast excess to simulate the conditions used in the commercial separation of heavy and precious metal ions. Our results suggest that divalent chlorometalate adsorption is a two-step process and that the divalent anions preferentially adsorb at the interface despite having a charge/volume ratio lower than that of chloride. These results provide fundamental insight into the structural mechanisms that underpin transport in phases that are relevant to heavy and precious metal ion separations, explaining the high efficiency of low charge density ion transport processes in the presence of charge dense anions.
Keywords: X-RAY REFLECTIVITY; SOLVENT-EXTRACTION; HYDRATION; LANTHANIDE; INTERFACE; COMPLEXES; DYNAMICS; METALS; LAYERS; PROBE; Chemistry; Materials Science